2018
DOI: 10.1177/2309499018802514
|View full text |Cite
|
Sign up to set email alerts
|

Extensor carpi radialis longus tendon ball interposition arthroplasty for treatment of late-stage Kienböck’s disease: Short-term results of a novel technique

Abstract: The aim of this study was to evaluate short-term clinical and radiological results of extensor carpi radialis longus (ECRL) tendon ball arthroplasty for treatment of late-stage Kienbö ck's disease. Methods: We retrospectively reviewed data of 19 patients suffering from Kienbö ck's treated with ECRL tendon ball arthroplasty between December 2014 and December 2016. Patients' clinical functions were assessed using grip strength, range of motion (ROM) of the wrist, QuickDASH, Mayo wrist score, and visual analog sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Wrist kinematics and biomechanical studies demonstrated that the lunate plays a crucial role in wrist movement and joint stability [ 18 ]. Complete excision of necrotic lunate would cause damage to the dorsal radiocarpal ligament (DRC) and the dorsal intercarpal ligament (DIC), resulting in dysfunction of the proximal row carpal bone and proximal displacement of the capitate and stress concentration on the scaphoid, further accelerating the collapse of the carpal bones [ 13 ]. Therefore, reconstruction of the tendons is the first important thing after excision of the lunate.…”
Section: Discussionmentioning
confidence: 99%
“…Wrist kinematics and biomechanical studies demonstrated that the lunate plays a crucial role in wrist movement and joint stability [ 18 ]. Complete excision of necrotic lunate would cause damage to the dorsal radiocarpal ligament (DRC) and the dorsal intercarpal ligament (DIC), resulting in dysfunction of the proximal row carpal bone and proximal displacement of the capitate and stress concentration on the scaphoid, further accelerating the collapse of the carpal bones [ 13 ]. Therefore, reconstruction of the tendons is the first important thing after excision of the lunate.…”
Section: Discussionmentioning
confidence: 99%
“…1 Watson et al postulated that a pattern of carpal collapse and scaphoid rotatory deformity is seen in Kienböck's disease and emphasized that the maintenance of carpal height ratio (CHR) and correction of scaphoid alignment were essential in preventing progressive degenerative change at the radioscaphoid joint. 2 Lunate excision combined with limited wrist arthrodesis [3][4][5] or inserting a spacer 6,7 is a method of providing biomechanical support to the carpus. However, a literature review suggested that lunate excision's clinical outcomes are comparable to those of other conventional techniques, 8 and satisfactory results after >10 years have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of ligament reconstruction has been reported in recent years. 7 We assumed that the arthroscopic approach could not only remove the lunate from within the wrist joint, but also preserve the dorsal extrinsic carpal ligaments safely. This procedure can prevent the proximal migration of the capitate and stress concentration on the scaphoid without a spacer or limited wrist fusion.…”
Section: Introductionmentioning
confidence: 99%